Exploring the Barriers and Facilitators Experienced by Palliative Health Care Providers Working with Patients Experiencing Homelessness during the COVID-19 Pandemic - Claire Rollans; Justine Baek; Gary Bloch; Joyce Nyhof-Young; Trevor Morey; Naheed Dosani; Donna Spaner (Palliative Medicine Reports, 2023)
Background: Patients experiencing homelessness not only have higher rates of medical complexity, comorbidity, and mortality, but also face barriers to accessing palliative care services. In structurally vulnerable populations with palliative care needs, these barriers are compounded, creating significant challenges for both patients and providers that have important health equity implications. Objective: The aim is to explore the experiences of palliative care providers working with patients experiencing homelessness during the COVID-19 pandemic and understand the barriers they faced in providing care, as well as facilitators that aided in the success of their teams. Methods: Seven health care providers from two Canadian palliative outreach teams involved in delivering palliative care services to patients experiencing homelessness during the COVID-19 pandemic participated in audio-recorded and transcribed videoconferencing interviews. Analysis was completed using generic descriptive thematic analysis. Results: Five key themes were identified: (1) factors negatively impacting patient health, (2) use of technology, (3) care provider emotions, (4) care provider education and advocacy, and (5) outreach team factors. Conclusion: Identified barriers during the pandemic included worsening of existing patient vulnerabilities, as well as challenges incorporating technology into care. Providers faced increased emotional burden, with a rise in workload, stress, fear, and grief. However, several facilitators allowed teams to provide high-quality care to this vulnerable population, including team support, interprofessional collaboration, and advocacy and education initiatives. The outreach model also proved to be a highly flexible, resilient, and adaptable model for providing care during the COVID-19 pandemic.